(untitled) (Research, Society and Development, 2021)
The work on screen aims to investigate the historical and cultural development of São Mamede-Paraíba, as well as to investigate the cultural diversity of this city. In this perspective, this research, through exploratory research, of qualitative nature, deductive method, collection of bibliographic-documental data, proceeded in order to carry out an analysis about the development of the Municipality of São Mamede, highlighting the legal treatment about the heritage historical-cultural. In addition, the protection of the historical and cultural heritage was emphasized, especially with regard to the Verdes Patos Ecological Reserve, archaeological sites, Church of Nossa Senhora da Conceição and Vila de Picotes. Notwithstanding, the responsibilities of public policies by the State related to the preservation of such elements were highlighted. Finally, in view of the exposed problem, it was sought, based on constitutional statements, to clarify the need of the State, based on the defense of human rights and respect for the well-being of society, to seek the promotion of public policies as a way to protect the historical-cultural heritage.